Phenomenon-based learning with peer assessment learning model for Chinese college students in entrepreneurship education: A needs assessment study - Yue, Ye; Sitthiworachart, Jirarat; Ratanaolarn, Thanin (Edelweiss Applied Science and Technology, 2026)
Entrepreneurship education is central in higher education, yet many programs remain teacher-centered. To develop a more learner-centered approach, this study surveyed 364 students in Taiyuan, China, on learning needs, including phenomenon-based learning, peer assessment, entrepreneurial skills, and critical thinking, using the Priority Needs Index (PNI). Students strongly preferred experiential, real-world challenges (PNI=9.05) and expressed interest in AI-supported project learning (PNI=8.35). They also reported high needs for peer feedback for improvement (PNI=10.6) and for strengthening opportunity analysis, persuasive communication, teamwork, and critical evaluation of information (PNI=9.30). Based on these findings, the study proposed an eight-step Phenomenon-Based Learning with Peer Assessment model (PhBLPA). A focus group of five experts affirmed that its iterative cycles of feedback, revision, presentation, and reflection mirror entrepreneurial practice and can enhance students’ entrepreneurial skills and critical thinking, with generative AI as a supportive tool when used transparently and critically. This model offers a practical framework for renewing entrepreneurship pedagogy in Chinese higher education.